The “Cairo Accord”- Towards the Eradication of RHD: An Update - Kotit, Susy; Phillips, David I. W.; Afifi, Ahmed; Yacoub, Magdi (Frontiers in Cardiovascular Medicine, 2021)
Rheumatic heart disease (RHD) is the most common cause of acquired heart disease in children and young adults. It continues to be prevalent in many low- and middle-income countries where it causes significant morbidity and mortality. Following the 2017 Cairo conference “Rheumatic Heart Disease: from Molecules to the Global Community,” experts from 21 countries formulated an approach for addressing the problem of RHD: “The Cairo Accord on Rheumatic Heart Disease.” The Accord attempts to set policy priorities for the eradication of acute rheumatic fever (ARF) and RHD and builds on a recent series of policy initiatives and calls to action. We present an update on the recommendations of the Cairo Accord and discuss recent progress toward the eradication of RHD, including contributions from our own Aswan Rheumatic Heart Disease Registry (ARGI).